(3eaGgje CSGSjI aj Yde GdGLJeGYs - (3ajHQ, eGcSs; (3GdLhgQj, eMeOs; (3gdGd, UdGMs ((3GdbGgQIs (3GdeQcR Gdbhej ddJQLeIs, 2011)
(3jVe gPG GdcJGH GdaUd GdChd ef cJGH eGcS ajHQ GdCSGSj (B"(3GdGbJUGO hGdeLJeY(B" (3hbO hVY ajHQ aj cJGHg (B"(3eaGgje CSGSjI aj Ye GdGLJeGY(B" (3JUhQGJg GdJj JhUd EdjgG aj CKfGA Yedg dUjGZI (B"(3Yde GLJeGY Gdage(B". (3hbO CQGO ceG CTGQ aj GdebOeI Cf jUhZ CacGQg aj UhQI CTed hCHSW hbGHdI ddage bOQ GdEecGf(B. (3haj CKfGA Yedg Ydi hVY Jdc GdeNWhWI GdJj JMhj JUhQGJg Yf GdCfeGW GdLJeGYjI JMhdJ GdebOeI GdeNJUQI Yf GdeaGgje Edi LRA eSJbd Yf GdcJGH faSgs
1 3 12 20
Keywords: (3GdGLJeGY, Ydes; (3GdYdhe GdGLJeGYjIs